Impact of soil compaction on the engineering properties of potato tubers - Edrris, Mohamed K.; Al-Gaadi, Khalid A.; Hassaballa, Abdalhaleem A.; Tola, ElKamil; Ahmed, Khalid A. M. (International Journal of Agricultural and Biological Engineering, 2020)
A study on a 30 hm2 field was conducted to assess the variability in soil compaction and to investigate its effect on the engineering properties of potato tubers in terms of tuber shape and key dimensions (length, width and thickness) and resistance to penetration, rupture and shear forces. Three soil compaction levels were spatially correlated with the engineering properties of potato tubers through linear regression and ANOVA test. The three compaction levels included a low level (C1) ranging between 1.2-1.9 MPa, a medium level (C2) with compaction levels between 2.0-2.3 MPa and a high level (C3) ranging between 2.4-2.9 MPa. Results revealed that there were no significant changes in the key tuber dimensions corresponding to the variability in soil compaction. However, inverse linear relationships were observed between soil compaction and the key tuber dimensions with R2 values of 77%, 97% and 96% for length, width and thickness, respectively. Similarly, the soil compaction was shown to have no effect on the tuber resistance to compression and shear force. In contrast, the tuber resistance to penetration was significantly affected by soil compaction (p>F = 0.0012). Keywords: compaction, potato tubers, precision agriculture, potato engineering properties DOI: 10.25165/j.ijabe.20201302.4818 Citation: Edrris M K, Al-Gaadi K A, Hassaballa A A, Tola E, Ahmed K A M. Impact of soil compaction on the engineering properties of potato tubers. Int J Agric & Biol Eng, 2020; 13(2): 163–167.